Opinion 2481: Clausilia index Mousson, 1863, Clausilia semilamellata Mousson, 1863, Clausilia derasa Mousson, 1863 (Gastropoda, Stylommatophora, Clausiliidae): specific names conserved by suppression of the respective senior synonyms, Clausilia unilamellata Mousson, 1856, Clausilia multilamellata Mousson, 1856 and Clausilia firmata Mousson, 1856 - ICZN (Bulletin of Zoological Nomenclature, 2021)
The International Commission on Zoological Nomenclature has conserved the current usage of the specific names of three terrestrial snail species, Clausilia index Mousson, 1863, Clausilia semilamellata Mousson, 1863 and Clausilia derasa Mousson, 1863, by suppressing their respective unused senior synonyms Clausilia unilamellata Mousson, 1856, Clausilia multilamellata Mousson, 1856 and Clausilia firmata Mousson, 1856.
Keywords: Nomenclature; taxonomy; Gastropoda; Stylommatophora; Clausiliidae; Mucronaria; Index; Pravispira; Elia; Caucasus